Life history of Pygidiopsis crassus n. sp. (Trematoda, Digenea, Heterophyidae) in the neotropical region. - Ostrowski de Núñez, M. (1995)
The life cycle of Pygidiopsis crassus n. sp. was experimentally reproduced, starting from cercariae from naturally infected Littoridina parchappei collected from Lujan River and different ponds in Buenos Aires Province, Argentina. Metacercariae were found encysted in the body cavity of experimentally and naturally infected fishes Cnesterodon decemmaculatus and naturally infected Jenynsia lineata. Adults were obtained experimentally in chicks and mice. The natural host is unknown. The new species is compared with Pygidiopsis macrostomum Travassos 1928, from Rattus norvegicus and from Noctilio leporinus mastivus, differing in body and egg sizes, in the size relation of oral and ventral sucker and the shape of excretory vesicle.